Factors Mediating the Risk and Protective Psychological Health and Well-Being of Healthcare Workers: A Systematic Review - Baba Vajrala, Samatha Jyothi.K, Priya. R, Rajasekhar Reddy.P.M, Mounika, Sudesh Kumari, Kirubakaran. C (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The psychological health and well-being of healthcare professionals have become increasingly critical as they navigate the demands of a challenging and evolving healthcare landscape. This abstract summarizes a comprehensive study that investigates the complex interplay of risk and protective factors affecting the mental health of healthcare workers. By analyzing data from surveys, interviews, and psychological assessments, this research aims to identify the key stressors and resilience factors that influence the psychological health and overall well-being of healthcare professionals. Additionally, this study explores potential mediation strategies, such as mindfulness-based interventions and support programs, designed to mitigate the negative impacts of stress and bolster psychological well-being. The findings from this research contribute valuable insights to inform healthcare organizations, policymakers, and mental health practitioners in implementing evidence-based strategies to support the mental health and well-being of those dedicated to the healthcare profession.